Analysis of factors affecting employee turnover with career path as an intervening variable - Marlita, Devi; Lesmini, ⁠Lis; Handayani, Sri; Indriyati, Indriyati; Soekirman, Atong; Saribanon, Euis; Sihombing, Sarinah (Annals of Human Resource Management Research, 2025)
Purpose: The purpose of this study is to develop hypotheses regarding factors that influence employee turnover, with a particular focus on the land transportation sector in Indonesia. The land transportation industry is characterized by high employee mobility and operational demands, making turnover a critical issue that directly affects service quality, safety, and organizational sustainability. Understanding the underlying factors is therefore essential for designing effective human resource policies and reducing workforce instability. Methodology: This research adopts a descriptive qualitative approach through a literature review. Descriptive qualitative studies aim to systematically synthesize and interpret findings from previous research without relying on statistical data analysis (Creswell & Poth, 2018). Comparative analysis was used to identify patterns and relationships across multiple studies. The data were collected from academic sources such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Q2–Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2–5 Journals, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. Results: The review identifies ten key findings: work engagement, remuneration, and leadership directly affect both career path and turnover; career path itself strongly influences turnover; and work engagement and remuneration indirectly affect turnover through career path. Conclusions: Employee turnover depends on engagement, leadership, and career opportunities; strengthening these reduces turnover and enhances workforce stability in transportation. Limitations: Future research should include transportation data to strengthen findings. Contribution: This study enhances understanding of employee turnover by examining work engagement, remuneration, leadership, and career path.